2012
DOI: 10.1080/14680629.2012.735791
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing thermal properties of asphalt materials for heat storage and transfer applications

Abstract: The paper considers extending the role of asphalt concrete pavements to become solar heat collectors and storage systems. The majority of the construction cost is already procured for such pavements and only marginal additional costs are likely to be incurred to add the necessary thermal features. Asphalt concrete pavements are, therefore, designed that incorporate aggregates and additives such as limestone, quartzite, lightweight aggregate, copper slag and copper fibre to make them more conductive, or more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…The use of steel fibers in asphalt concrete is expected to improve mechanical performance and electrical conductivity of asphalt concrete. Dawson et al used additives such as limestone, quartzite, lightweight aggregate, copper fiber etc., and showed that copper fiber improved thermal conductivity slightly, replacing limestone with quartzite increased thermal conductivity up to 135%, and use of light weight asphalt could enable easier heat storage and lower pavement damage in freeze‐thaw cycle. Expanded polypropylene (EPP) pellet and graphite as additives to improve the performance of asphalt concrete were proposed by Shi who found that EPP as aggregate replacement is a better choice compared with the use of melted EPP as a binder modifier because it has good heat susceptibility and is hard to melt at the working temperature of the hot mixed asphalt.…”
Section: Materials For Pavement Energy Harvestingmentioning
confidence: 99%
“…The use of steel fibers in asphalt concrete is expected to improve mechanical performance and electrical conductivity of asphalt concrete. Dawson et al used additives such as limestone, quartzite, lightweight aggregate, copper fiber etc., and showed that copper fiber improved thermal conductivity slightly, replacing limestone with quartzite increased thermal conductivity up to 135%, and use of light weight asphalt could enable easier heat storage and lower pavement damage in freeze‐thaw cycle. Expanded polypropylene (EPP) pellet and graphite as additives to improve the performance of asphalt concrete were proposed by Shi who found that EPP as aggregate replacement is a better choice compared with the use of melted EPP as a binder modifier because it has good heat susceptibility and is hard to melt at the working temperature of the hot mixed asphalt.…”
Section: Materials For Pavement Energy Harvestingmentioning
confidence: 99%
“…Previous work has focused largely on the temperature gradient for the full depth of road [36,37]. However, the temperature gradient within road surface layer, especially the depth from 0 mm to 100 mm, is more valuable for pavement thermoelectric generation technology due to the presence of greater and longer temperature difference [38,39].…”
Section: Temperature Gradient Within Road Pavementmentioning
confidence: 99%
“…The results showed that tail water temperature of 40°C or above was capable of melting snow on the pavements, depending on weather conditions and melting requirements. Dawson, Dehdezi, Hall, Wang, and Isola (2012) considered enhancing the thermal properties of asphalt materials for solar heat collectors and storage systems. As a result, adding aggregates and additives such as limestone, quartzite, copper slag, and copper fibre makes them more conductive.…”
Section: Introductionmentioning
confidence: 99%